Vocabulary Is an Appropriate Measure of Premorbid Intelligence in a Sample with Heterogeneous Educational Level in Brazil - Maira Okada de Oliveira; Ricardo Nitrini; Mônica Sanches Yassuda; Sonia Maria Dozzi Brucki (Behavioural Neurology)
Crystallized intelligence refers to one’s knowledge base and can be measured by vocabulary tests. Fluid intelligence is related to nonverbal aspects of intelligence, depends very little on previously acquired knowledge, and can be measured by tests such as Block Design (BD) and Raven Colored Matrices (RCM). Premorbid intelligence quotient (IQ) refers to one’s intellectual ability level previous to the onset of disorders like mild cognitive impairment (MCI) and Alzheimer’s disease (AD) and it is important to estimate disease severity. The objective was to compare performance in tests that measure crystallized and fluid intelligence in healthy subjects and patients with amnestic MCI (aMCI) and AD. One hundred forty-four participants (aMCI (n=38), AD (n=45), and healthy controls (n=61)) were submitted to neuropsychological tests (WAIS-III vocabulary, BD, and RCM). There were significant among groups, except for vocabulary, indicating a relative stability of crystallized intelligence in the continuum from normal to pathological cognitive decline. Vocabulary seems to be stable during the progression of the disease and useful as a measure of premorbid intelligence, that is, to estimate previous function in relation to the level of education and, as a collateral measure of cognition in people with low education.